Evaluation of the validity and reliability of the entrapment scale in Iranian adolescents and Its relationship with suicidal ideation - Kulemarzi, Mohammad Javad Bagian; Moosivand, Mahboobeh; Zaremohzzabieh, Zeinab (SAGE Publications Inc., 2024)
This explored key aspects of the Integrated Motivational Volition theory in adolescents, particularly during a period when they experience significantly higher rates of suicidal ideation. The authors focused on assessing the validity and reliability of the Entrapment Scale among Iranian adolescents. The sample included 623 adolescents. The authors evaluated the scale's reliability and validity. The analysis revealed that Entrapment Scale demonstrated strong internal consistency, indicating that it consistently measured the concept of entrapment. The relationships between Entrapment Scale scores and depression, anxiety, hopelessness, defeat, and suicidal ideation were also found to be significant. This suggests that Entrapment Scale is a valid tool for assessing entrapment in this context. We also determined an optimal cut-off value of 18 on the Entrapment Scale, which showed a high sensitivity of 98 in identifying those at risk of entrapment-related issues, with a specificity of 73.6 in correctly identifying those without such issues. The study confirmed the structure of the Entrapment Scale remains consistent with its original form when applied to the adolescent population. Overall, the findings indicate that the Persian version of the Entrapment Scale is a reliable and valid tool for evaluating entrapment among Iranian adolescents.